Shared decision making within goal setting in rehabilitation settings: A systematic review. Issue 1 (January 2017) - Rose, Alice; Rosewilliam, Sheeba; Soundy, Andrew
Highlights: Currently SDM within goal-setting is limited. Patients vary in how much involvement they wish to have in goal-setting. Involvement in decisions about their goals increased patient motivation. Staff recognised the benefits of this approach however reported various barriers. Patients and staff need to be further educated about this new healthcare approach. Abstract: Objective: To map out and synthesise literature that considers the extent of shared decision-making (SDM) within goal-setting in rehabilitation settings and explore participants' views of this approach within goal-setting. Methods: Four databases were systematically searched between January 2005–September 2015. All articles addressing SDM within goal-setting involving adult rehabilitation patients were included. The literature was critically appraised followed by a thematic synthesis. Results: The search output identified 3129 studies and 15 articles met the inclusion criteria. Themes that emerged related to methods of SDM within goal-setting, participants' views on SDM, perceived benefits of SDM, barriers and facilitators to using SDM and suggestions to improve involvement of patients resulting in a better process of goal-setting. Conclusions: The literature showed various levels of patient involvement existing within goal-setting however few teams adopted an entirely patient-centred approach. However, since the review has identified clear value to consider SDM within goal-setting for rehabilitation, further research is required and practice should consider educating both clinicians and patients about this approach. Practice implications: To enhance the use of SDM within goal-setting in rehabilitation it is likely clinicians and patients will require further education on this approach. For clinicians this could commence during their training at undergraduate level.